Nucleotide polymorphism assay for the identification of west African group Bacillus anthracis: a lineage lacking anthrose - Diansy Zincke (BMC Microbiology, 2020)
Abstract Background The exosporium of the anthrax-causing Bacillus anthracis endospores display a tetrasaccharide composed of three rhamnose residues and an unusual sugar termed anthrose. Anthrose is a proposed potential target for immunotherapy and for specific detection of B. anthracis. Although originally thought to be ubiquitous in B. anthracis, previous work identified an anthrose negative strain from a West African lineage isolated from cattle that could represent a vaccine escape mutant. These strains carry genes required for expression of the anthrose operon but premature stop codons resulting from an 8-bp insertion in BAS3320 (an amino-transferase) and a C/T substitution at position 892 of the BAS3321 (a glycosyltransferase) gene prevent anthrose expression. Various other single nucleotide polymorphisms (SNPs) have been identified throughout the operon and could be the basis for detection of anthrose-deficient strains. Results In this study, we evaluated rhAmp genotypic assays based on SNPs at positions 892 and 1352 of BAS3321 for detection and differentiation of anthrose negative (Ant−) West African strains. Discrimination of anthrose negative West African isolates was achieved with as low as 100 fg of DNA, whereas consistent genotyping of Sterne necessitated at least 1 pg of DNA. Conclusions Screening of a global panel of B. anthracis isolates showed anthrose-expressing alleles are prevalent worldwide whereas the anthrose-deficient phenotype is to date limited to West Africa. Our work also revealed a third, previously unreported anthrose genotype in which the operon is altogether missing from a Polish B. anthracis isolate.